Applying Constructivism Principles to Enhance Digital Media Literacy in Higher Education - Hariyati, Mutty; Nursalim, Mochamad; Fitri, Ruqoyyah; Heriyanto,; Destrianto, Mochammad Riski (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study explores the application of constructivist principles in the development of digital media literacy within higher education. Constructivism and digital media literacy share foundational elements, including active participation, critical thinking, contextual learning environments, and social collaboration. This research employs a qualitative approach through a literature review. Publications from 2014 to 2024 were selected based on their relevance to constructivist learning theory and digital media literacy, resulting in four core sources analyzed. The findings demonstrated that constructivist principles significantly contribute to the enhancement of digital media literacy skills, particularly in the areas of content creation, information management, digital publishing, and critical engagement. These competencies were essential for fostering independent, reflective, and responsible learners. The study concludes that constructivist-based approaches are vital for effectively integrating digital media literacy into higher education. To support this integration, it is recommended that universities embed digital media literacy into curricular frameworks and provide additional resources such as training programs through university libraries. These libraries, as central information hubs, can play a pivotal role in supporting students’ digital literacy development and promoting lifelong learning.